Computer Adaptive Test Development To Assess Students’ Psychology - Phan Thi Thu Nguyet (Universitas Serambi Mekkah, 2021)
Psychology stability plays great role in students’ learning, and stress becomes asignificantly serious issue among university students. An efficient tools isneeded to understand it more. The aim of present study is to develop aComputerized Adaptive Testing (CAT) as pioneer project in South East Asia,and starting in Vietnam. In this vein, an item bank of 68 items has beenconstructed, which is based on Likert Polytomous Scales through five subdomains: behavior, academic performance, family, lecturer and finance. It hasassessed 2,085 students (704 males and 1,381 females). MultidimensionalRandom Coefficients Multinomial Logit (MRCML) Model is applied todevelop Multidimensional Stress Scales and Computerized Adaptive Testingprocedure. The result findings indicate that Multidimensional RandomCoefficients Multinomial Logit (MRCML) can be used to develop new scalewith psychometric properties. Indicated by various fit criteria MNSQ, standarderrors, Z (t-test) implemented in software ConQuest. The sub-domain has agood reliability (from .857 to .798). As respect to CATs, a simulated experiment based on the empirical data is applied to evaluate the performance of the proposed computerized adaptive testing. The standard error of the estimated stress proficiencies are reported in this study. The 68 items stress data appropriate fit the Multidimensional model applied.